Morphological Growht of Oil Palm on Biomass-Amended Post-Coal-Mining Land - Romadhon Nur Rohim; Sutan Tarmizi Lubis; Agung Lesmana; Arjuna Manurung; Muhammad Aqwan A. U; Said Asyrof Auvvarof (Jurnal Biologi Tropis, 2026)
Post-coal mining land generally has low soil fertility due to the degradation of physical, chemical, and biological soil properties, which limits the growth of oil palm (Elaeis guineensis Jacq.). This study aimed to evaluate the effectiveness of oil palm biomass-based ameliorants on the morphological growth of immature oil palm planted on post-mining land using mineral soil as a comparison. The study was conducted at PT Pola Kahuripan Inti Sawit, Tanah Laut Regency, South Kalimantan, from November 2025 to January 2026 using a quantitative-comparative survey method. The treatments consisted of P1 (150 kg plant⁻¹ empty fruit bunches on mineral soil), and P2 (150 kg plant⁻¹ empty fruit bunches + 30 kg plant⁻¹ boiler ash) on post-mining land. Observed parameters included plant height, stem diameter, frond number, male flowers, female flowers, and abortive flowers at 12–14 months after planting. Data were analyzed using an independent sample t-test at a 5% significance level. The results showed that P2 increased vegetative growth in post-mining land, with a plant height of 226.62 cm, a stem diameter of 19.12 cm, and 29.82 fronds at 14 months after planting, approaching growth on mineral soil. The combination of empty fruit bunches and boiler ash has the potential to be an effective remedial material for sustainable rehabilitation of post-coal mining land.